ANALISIS PENGARUH TEKNIK FOTOGRAFI TERHADAP CITRA MEREK DALAM IKLAN PRODUK: Analysis of the Influence of Photography Techniques on Brand Image in Product Advertising - Hendi Sama; Kenny Wilson; Syaeful Anas Aklani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
This research aims to fill the knowledge gap and comprehensively analyze the impact of photographic techniques on brand image in product advertising. Illumination, motion effects, focus and sharpness, as well as composition, have been identified as key factors that significantly influence how consumers perceive and accept brands through advertising media. The quantitative research method, specifically simple random sampling and causal-comparative were used in this study to collect and analyze data from a number of respondents involved in the research. The carefully conducted and valid data analysis using SPSS 26 software confirms that photographic techniques have a significantly positive impact on brand image in product advertising. This research has highly relevant implications for marketing and advertising practitioners seeking to enhance the effectiveness of their product advertising. With a deeper understanding of how photographic techniques influence brand image, practitioners can design more captivating and influential advertisements, thus shaping consumer perceptions more effectively. This study provides a crucial contribution to understanding the essential role of photography in shaping brand image, which is now more relevant than ever in an era of marketing that is increasingly focused on visual elements and digital media.